Kenaf/glass fiber-reinforced polymer composites: Pioneering sustainable materials with enhanced mechanical and tribological properties - Supian A.B.M.; Asyraf M.R.M.; Syamsir A.; Ma Q.; Hazrati K.Z.; Azlin M.N.M.; Mubarak Ali M.; Ghani A.; Hua L.S.; SaifulAzry S.; Razman M.R.; Ramli Z.; et al. (John Wiley and Sons Inc, 2025)
Hybrid kenaf/glass fiber reinforced polymer composites have emerged as promising structural materials, garnering significant attention due to their unique blend of natural kenaf fibers and synthetic glass fibers. However, despite their potential, there remains a gap in the comprehensive understanding of their quasi-static mechanical behavior, creep resistance, and fatigue performance. This paper addresses this gap by presenting recent advancements in studying these key properties of hybrid composites. Studies reveal that the combination of kenaf and glass fibers results in enhanced tensile, flexural, and impact strengths compared to individual fiber composites. Additionally, the hybridization offers improved creep resistance, with the glass fibers reinforcing the polymer matrix against deformation under sustained loads. Furthermore, investigations into fatigue properties demonstrate the resilience of hybrid composites to cyclic loading, contributing to prolonged service life in high-stress environments. By elucidating the interplay between kenaf and glass fibers, this review underscores the potential of hybrid composites in various structural applications. The synergistic effects between natural and synthetic fibers offer a balance between sustainability, performance, and durability, making hybrid kenaf/glass fiber reinforced polymer composites a compelling choice for industries seeking lightweight, high-performance materials in which aligns with the sustainable development goals (SDGs) especially on Goal 12. Highlights: In composite engineering, combining glass and kenaf fibers could cut production costs, yield high-performance materials, and promote green technology. Substituting part of the glass fiber with kenaf can enhance the strength-to-weight ratio and promote greater biodegradability in current synthetic composites. Quasi-mechanical properties of hybrid kenaf/glass-based composites was enhanced by optimal stacking sequences, filler addition, and fiber treatment. Failures due to fatigue and creep can be reduced by hybridizing kenaf/glass fiber composites can prevent in polymer composite due to enhance elastic modulus. Enhanced tribological performance of hybrid kenaf/glass-based composites due to less damage in microstructure via good interlocking of kenaf and glass in matrix. ? 2024 Society of Plastics Engineers.